2013
DOI: 10.1371/journal.pone.0067953
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Common Deletion, a Potential Biomarker for Cancer Occurrence, Is Selected against in Cancer Background: A Meta-Analysis of 38 Studies

Abstract: Mitochondrial dysfunction has been long proposed to play a major role in tumorigenesis. Mitochondrial DNA (mtDNA) mutations, especially the mtDNA 4,977 bp deletion has been found in patients of various types of cancer. In order to comprehend the mtDNA 4,977 bp deletion status in various cancer types, we performed a meta-analysis composed of 33 publications, in which a total of 1613 cancer cases, 1516 adjacent normals and 638 healthy controls were included. When all studies were pooled, we found that cancerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 61 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…Multiple reports have associated the occurrence of this mtDNA common deletion with a wide range of cancer types including breast cancer (Lu et al, 2009; Nie et al, 2013). Investigations involving cell lines further implicated the common deletion in apoptosis and tumorigenesis (Lee et al, 2007; Wang and Lu, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple reports have associated the occurrence of this mtDNA common deletion with a wide range of cancer types including breast cancer (Lu et al, 2009; Nie et al, 2013). Investigations involving cell lines further implicated the common deletion in apoptosis and tumorigenesis (Lee et al, 2007; Wang and Lu, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increasing evidence suggests that mitochondrial function is severely impaired in various cancers including breast cancer (Deus et al, 2014; Neuzil and Moreno-Sanchez, 2013) due to genetic defects in the OXPHOS system (Chandra and Singh, 2011). Consequently, mtDNA mutations have been recognized as an important aspect of breast cancer occurrence and development (Nie et al, 2013; Shen et al, 2010; Shen et al, 2011; Yu et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In studies on other cancers [25,27], ∼5 kb deletion was found to be consistently lowered in cancer tissues; this deletion was detected in 24 % of the breast tumors, 52 % of the colorectal tumors, 79 % of the gastric tumors, and 40 % of the head and neck tumors as compared with 77, 83, 100, and 90 % of the adjacent respective non-tumor tissues [36]. In a meta-analysis on different cancers, ∼5 kb deletion was found to be less in cancer tissues compared to adjacent or matched normal tissues [37]. In another study on oral cancer and precancer tissues, not only this specific deletion was found to be lower in cancer tissues; a trend was observed in this lowering from controls to precancers to cancerous tissues [26].…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence suggesting that mitochondria may serve as potential contributors to carcinogenesis even though the exact mechanism of how mitochondria involved is still debatable and is not welldocumented. Thus, mtDNA is now being targeted organelle by an increasing number of laboratories in order to investigate its potential role as biomarker for tumorigenesis in various types of tissues [86,87].…”
Section: Mitochondrial Dna Mutations In Cancermentioning
confidence: 99%